Peran Perilaku Keuangan dalam Meningkatkan Kesejahteraan Keuangan di Era Digital - Dania Febriana; Wida Purwidianti; Sri Wahyuni; Bima Cinintya Pratama (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - The purpose of this study is to analyze the influence of digital financial literacy and financial inclusion on the financial well-being of female MSME actors, with financial behavior as a mediating variable Method - The method used is a quantitative approach with the SEM-PLS 3 analysis technique. The data was collected through a questionnaire distributed to 100 female MSME actors in three regencies in the Java Tengan region (Cilacap, Purbalingga and Banyumas). Main Findings - This study proves that digital financial literacy has a direct and indirect effect on financial well-being through financial well-being. Direct and mediated effects were not found on the relationship between financial inclusion and financial well-being Theory and Practical Implications -This study has implications for the development of planned behavior theory, especially the financial behavior of MSME owners. The research provides policy implications to stakeholders in the development of women MSMEs Novelty - The novelty of this research lies in testing financial behavior as a mediating variable between digital financial literacy and financial inclusion in financial well-being